Vigilância genômica das variantes emergentes do SARS-CoV-2 em cidades do território brasileiro - Silva, Thauane de Oliveira (2023)
Introduction: In December 2019, Chinese authorities detected a new type of virus that can cause infections in humans. Since the emergence of SARS-CoV-2, researchers have monitored its mutations, genome traits, evolution and behavior of the virus through different tools used within the scope of genomic surveillance.Objective: To evaluate the introduction and circulation of emerging variants of SARS-CoV-2 in five cities in Brazil (Niterói-RJ, Campo Grande-MS, Dourados-MS, Rondônia-RO, Recife PE). Methods: The present study is a descriptive, analytical, cross-sectional observational research, with primary data submitted to laboratory techniques from samples positive for SARS-CoV-2 infection. The phylogenetic analysis comprised identified isolates and a representative set of viral diversity in a high-likelihood tree using Viral MSA and QI-TREE2 tools.12 Clinical data, Ct values, and serology were collected to compare the frequency of these variables in individuals affected by Variants of Concern (VOC) compared to other SARS-CoV-2 strains regarding transmissibility, clinical symptoms, and immune escape. Results: We included 209 individuals, mostly women, with a mean age of 39.8±13.5 years and of white color. Thirteen circulating strains were identified from October 2020 to May 2021. The most frequent variants were P.2 (46,4%), followed by P.1(22%) and B.1.133 (11,4%). VOC showed a lower Ct value than other strains, which may signify greater viral transmission. Individuals affected by VOC showed seroconversion in a lower proportion than the other strains. Conclusion: Contextualizing the sequenced genomes allowed us to analyze the geographic spread and viral dynamics on local, regional, and national scales. Although genome sequencing has been performed on an unprecedented scale, knowledge gaps still need to be filled to understand the natural history of SARS-CoV-2 and its global effects.